Assessment Of Riverbank Stability In Perak River Induced By Unsustainable Sand Mining Activities - Othman, Muhammad Zaki (Universiti Sains Malaysia, 2022)
For many years, both roads and buildings have been built using aggregates like sand and gravel. Because of the enormous growth that has occurred in recent decades, river sand has increased in demand as a building material during the past several years. Therefore, sand mining activities had been increasing rapidly. Without good monitoring from authorities, sand mining had caused many problems such as riverbank erosion, destroy river buffer zone and many more. The objective of this research is to identify riverbank stability during low flow and high flow and factors that causing riverbank to erosion. By using resistivity test it can help determine if the study region has adequate soil, and the equipment can measure the subsurface profile up to 80 metres below the ground surface. The higher the resistivity means the soil properties are more stable. When compared to conditions with a high flow, low flow conditions have been shown to have superior riverbank stability. These findings are based on the findings of study. Conditions of high flow have a greater flowrate as compared to conditions of low flow, which are gradually generating riverbank erosion. In addition, this study was successful in determining that changes in water level, changes in soil qualities, and sand mining are the primary factors that contribute to riverbank erosion. Positive findings emerged from the administration of the surveys and the subsequent examination of the data that was gathered. The utilisation of this strategy will allow for the mitigation of the damaging effects that are caused by sand mining activities, hence preserving the river.